Theoretical investigation of different CPVT configurations based on liquid absorption spectral beam filter. (15th December 2019) - Adam, Saadelnour Abdueljabbar; Ju, Xing; Zhang, Zheyang; Abd El-Samie, Mostafa M.; Xu, Chao
Abstract: Concentrated photovoltaic/thermal (CPVT) hybrid systems can provide a simultaneous supply of electrical and thermal energy. The performance of CPVT system based on liquid absorption spectral beam filter with different structure configurations is theoretically investigated in this paper. Main efforts are put to reveal the effects of vacuum enclosure surrounding the optical filter and the heat transfer medium between the thermal receiver and the solar cells on the system performance at different operating conditions. The effect of long-term operation under high-temperature exposure is also analyzed. The simulation results show that both the vacuum enclosure around the thermal unit and the heat transfer medium between the thermal receiver and solar cells can influence the transmitted energy arriving the solar cells and the temperature of the whole module, which are very sensitive to the electrical and thermal performance. The use of vacuum enclosure decreases the electrical efficiency by about 4%, while it leads to a much higher thermal efficiency. With large coolant flow rates, the configuration without the vacuum enclosure shows both higher overall energy and exergetic efficiencies. It is also suggested to use an air gap between the receiver and PV cells instead of a vacuum layer or a solid layer. Highlights: The performance of CPVT device based on liquid absorption spectral beam filter with different structures is presented. The use of a vacuum enclosure reduces the radiation for electrical conversion while increases the thermal efficiency. An air gap between the receiver and PV cells is recommended to be used. Effects of concentration ratio and fluid flow rate on the energy and exergetic efficiencies are presented.